Trakoma: Penyakit Tropis Terabaikan - Ghiffari, Fahman; Himayani, Rani (Medula, 2024)
Trachoma is a neglected tropical disease. Trachoma is an infection of the eye caused by bacteria Chlamydia trachomatis. This disease often attacks people who live with low economic income with a bad environment. This infection is transmitted through physical contact and from animals to humans. Trachoma can be classified into an active or infectious phase and a chronic or non-infectious phase. According to its level, trachoma has six types of grades in the assessment of clinical symptoms of trachoma namely stage Normal Tarsal Conjunctiva (N), stage Trachomatous inflammation-Follicular (TF), stage Trachomatous inflammation-Intense (OF), stage Trachomatous Scarring (TS), stage Trachomatous Trichiasis (TT), and stage Corneal Opacity (CO). Treatment that can be done to treat trachoma is the SAFE program developed by WHO, including: surgery (surgery),antibiotics (antibiotics),facial cleanliness (facial cleansing), and environmental improvement (environmental improvement). This article uses the method literature review from various national and international journal references with the following search keywords: trachoma, etiology, classification, management, and Chlamydia trachomatis.